A Miniature State: The Dollhouse City of Princess Augusta of Schwarzburg (1666–1751). (December 2015) - Cremer, Annette
Abstract : During the first half of the eighteenth century, Princess Augusta of Schwarzburg established a large collection of dollhouses which resembled the interior decoration and furniture of her palace in Thuringia. Several hundred dolls represented herself, members of her dynasty, courtiers and the people around her. Today, it gives us an almost encyclopaedic picture of life in a small German princely residence. This article describes how this world in miniature came into existence. It examines its various functions in respect to the political, confessional and socio-cultural background of Princess Augusta and her husband Count Anton Günther II of Schwarzburg. The Mon Plaisir collection sheds light on the self-conception by which smaller courts made use of a cultural tradition as a political instrument within the system of the Holy Roman Empire.